Penerapan E-Government melalui Sistem Informasi Pemerintahan Daerah (SIPD) dalam Penyelenggaraan Pemerintahan Daerah di Kabupaten Lebak Tahun 2024 - Nazwa Alia Firdaus; Neneng Yani Yuningsih (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
(The Implementation of E-Government Through the Regional Government Information System (SIPD) in the Administration of Local Government in Lebak Regency in 2024) Penerapan e-government melalui Sistem Informasi Pemerintahan Daerah (SIPD) yang dikelola Kementerian Dalam Negeri digunakan Pemerintah Kabupaten Lebak melalui Badan Perencanaan Pembangunan, Riset, dan Inovasi Daerah (Bapperida) dan Badan Keuangan dan Aset Daerah (BKAD) sebagai instrumen utama dalam perencanaan pembangunan serta pengelolaan keuangan daerah. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan teknik wawancara, dokumentasi, dan studi literatur. Analisis penelitian didasarkan pada teori tiga elemen sukses e-government dari Harvard JFK School of Government yang dikembangkan oleh Indrajit (2006) yaitu support, capacity, dan value. Hasil penelitian menunjukkan bahwa penerapan SIPD telah mendapat dukungan regulasi, alokasi anggaran dari APBN dan APBD, serta komitmen pemerintah daerah melalui penguatan SDM dan koordinasi lintas perangkat daerah. Dari aspek kapasitas, ketersediaan sumber daya manusia dinilai cukup memadai meskipun tetap memerlukan peningkatan pelatihan berkelanjutan. Dari aspek manfaat, SIPD memberikan dampak positif bagi pemerintah dengan meningkatkan transparansi, akuntabilitas, dan efisiensi tata kelola, serta bagi masyarakat melalui kemudahan dalam menyampaikan aspirasi pembangunan meskipun akses partisipasi masih terbatas. Abstract The implementation of e-government through the Regional Government Information System (SIPD managed by the Ministry of Home Affairs, has been adopted by the Regional Development Planning, Research, and Innovation Agency (Bapperida) and the Regional Financial and Asset Agency (BKAD) of Lebak Regency as the main instrument for development planning and financial management. This research employs a qualitative descriptive approach using interviews, documentation, and literature review. The analysis is based on the three elements of successful e-government implementation developed by the Harvard JFK School of Government: support, capacity, and value. The findings indicate that SIPD implementation has received strong regulatory backing, adequate budget allocation from both national and regional sources, and commitment from the local government through cross-agency coordination and human resource allocation. In terms of capacity, the availability of human resources is relatively sufficient, although continuous training remains necessary to adapt to system updates. Regarding value, SIPD has provided significant benefits by improving transparency, accountability, and efficiency in governance, while also enabling public participation through the submission of development proposals, although the level of Lebak Regency has shown promising progress.